The B-cell response to a primary and booster course of MenACWY-CRM197 vaccine administered at 2, 4 and 12 months of age - Blanchard-Rohner, G; Snape, MD; Kelly, D; O'Connor, D; John, T; Clutterbuck, E; Ohene-Kena, B; Klinger, C; Odrljin, T; Pollard, A (2013)
A quadrivalent meningococcal vaccine conjugated to CRM197 (MenACWY-CRM197) is immunogenic in young infants. We assessed the memory B-cell and antibody responses after a primary and booster course of MenACWY-CRM197 in children. At 5 months of age, following primary immunisation, serogroup-specific memory B-cells were detectable in fewer than 25% of children, although protective antibody titres (hSBA≥4) were detectable in 69% of children against serogroup A and more than 95% against the other serogroups. At 12 months, before booster immunisation the percentages with hSBA≥4 were 5% for serogroup A, and between 44 and 70% for the other serogroups. One month after booster immunisation with MenACWY-CRM197 over 50% of children had detectable memory B-cells, and 91% had hSBA≥4 against serogroup A and more than 99% against the other serogroups. These data show that few antigen-specific anticapsular memory B-cells can be detected after two-doses priming with MenACWY-CRM197. For MenC and CRM197, the antigens with the highest number of B-cells at 5 months, there was a definite (p≤0.02) but weak correlation with antibody persistence at 12 months. Although previous studies suggest that measuring memory B-cell responses after priming immunisations in infancy can be used to predict antibody persistence and memory responses, this may not be suitable for all antigens in young children. © 2013 Elsevier Ltd.